2022
DOI: 10.1002/star.202200184
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Properties of Millet Starches as Influenced by Different Modification Techniques: A Review

Abstract: The growing need for new starches has sparked interest in the expansion of novel starch sources for the food sector. Millets are popular due to various health benefits and sustainability. Similar to the majority of cereals, the major constituent and quality factor of millet grain is its starch, which contributes 60-70% of the whole grain. Utilization of starch is reliant on its structural and functional properties. Starch in its native form does not possess all the required properties such as low temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
(177 reference statements)
0
5
0
Order By: Relevance
“…Millets have less swelling power than traditional starches like wheat and rice, which may limit their applications. The resistant starch content of millet starch varies, with low RS content millets being advantageous for easily digestible food formulations, including those for infants and convalescents, and high resistant starch content millets with greater paste viscosities and low ability to retrograde being suitable for a variety of food applications, similar to waxy corn starch [ 17 , 28 ].…”
Section: Applications and Limitations Of Native And Modified Millet S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Millets have less swelling power than traditional starches like wheat and rice, which may limit their applications. The resistant starch content of millet starch varies, with low RS content millets being advantageous for easily digestible food formulations, including those for infants and convalescents, and high resistant starch content millets with greater paste viscosities and low ability to retrograde being suitable for a variety of food applications, similar to waxy corn starch [ 17 , 28 ].…”
Section: Applications and Limitations Of Native And Modified Millet S...mentioning
confidence: 99%
“…There are several types of thermal and non-thermal techniques, such as physical, chemical, biological, pre-gelatination, and heat moisture treatment, are used for the modifications of starch to improve their physico-chemical and functional properties, such as imparting thermal stability and decrease retrogradation. In this regard, the non-thermal techniques of starch modifications are emerging innovative techniques, gaining more importance due to their eco-friendly sustainability and use of low energy [ 28 ]. Barbhuiya et al [ 29 ] reviewed and reported that the non-thermal techniques are one of the innovative emerging techniques; that can be replaced by the thermal processing technologies, which improved the structural components of food and food products with desirable functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of researchers conducted an analysis comparing various types of millet starches, but, unfortunately, they did not provide a thorough study of proso millet starch (PMS) [ 6 , 16 , 17 ]. According to Banger et al [ 18 ], a comprehensive account of PMS, including its physiochemical and functional properties, modification, and applications, was presented.…”
Section: Introductionmentioning
confidence: 99%
“…These reviews carry overall information on the various processing techniques and their impact on the millet grains or their flours. Most reviews on the impact of hydrothermal processing of millet grains are limited to the treatment given to its flour or its starch (Mahajan et al, 2021; Punia et al, 2021; Sruthi & Rao, 2021; Thakur et al, 2023). The impact of processing on specific varieties of millet starches has also been reviewed by various researchers (Punia et al, 2021; Rathore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%